Review of Tafsir Al-Munir Fi Al-Syari'ah Wa Al-'Aqidah Wa Al-Manhaj Creation Wahbah Azzuhaili - Huda, Nana Najatul (UIN Sunan Gunung Djati Bandung, 2023)
Tafsir al-Munir fi al-Syari'ah wa al-'Aqidah wa al-Manhaj is a book of interpretations written by a religious expert who graduated from 'Ain al-Syam University in Egypt with a focus on the field of law. He was born in the village of Dir 'Atiyyah, Faiha sub-district, Damascus, Syria. His purpose in writing this book was as a form of admiration and love for the Koran itself, because according to him, the Koran has a very close bond with the needs of modern life and cultural and educational demands. This interpretation has a fiqh style, namely interpreting the Qur'an more broadly in terms of Islamic law. The source of the interpretation is by combining bi ma'tsur (hiwayah) and bi al-Ra'yi (opinion and ijtihad). The method of interpretation uses tahlili, namely interpreting the Qur'an according to the order of the Mushaf by collaborating with the thematic method. Therefore, it is important for us as Muslim students to know the methodology and style of a book of interpretation, as well as the reasons for mufasir scholars in writing their works, in order to know what the aims of the mufasir figures who have spent a lot of time in their lives making their writings in a knowledge of the Qur'an and interpretation. This research method is qualitative through literature review. The results and discussion of this study is that there is a fiqh pattern due to the scientific background of the interpreters in the field of fiqh, so that the direction of interpretation is more extended to shari'ah or fiqh law, methods of interpretation in tahlili and semi-thematic ways and sources of interpretation with fi al-Ma'tsur and bi al-Ra'yi. This study concludes that this interpretation was written by Wahbah Azzuhaili due to his admiration and love for the Qur'an because the Qur'an has strong ties to the necessities of life and educational demands.